1983
DOI: 10.1002/bit.260250212
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of acyl transfer by penicillin acylases

Abstract: The hypothesis that at least some penicillin acylases react via an acyl-enzyme intermediate was tested by kinetic investigations involving the methyl ester of cyanoacetic acid as the acyl donor, deacetyl-7-aminocephalosporanic acid as the acyl receptor, and penicillin acylase (E.C.3.5.1.11) from B. megaterium ATCC 14945 as the catalyst. The results obtained at low concentrations of the acyl receptor are in accord with the derived rate equations. Deviations observed at higher concentrations of the acyl receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…It is based on the use of an activated acyl donor (as ester or amide) to form an acyl-enzyme intermediate that may be further deacylated by the antibiotic nucleus (Fig. 3) to yield the desired antibiotic [4,[49][50][51]. That is, KCS may be carried out only if this acylenzyme is formed, as in the case of all PGA described to date.…”
Section: Kinetically Controlled Synthesis (Kcs)mentioning
confidence: 99%
“…It is based on the use of an activated acyl donor (as ester or amide) to form an acyl-enzyme intermediate that may be further deacylated by the antibiotic nucleus (Fig. 3) to yield the desired antibiotic [4,[49][50][51]. That is, KCS may be carried out only if this acylenzyme is formed, as in the case of all PGA described to date.…”
Section: Kinetically Controlled Synthesis (Kcs)mentioning
confidence: 99%
“…Although the substrate specificity (Margolin et al 1980) and the kinetic mechanism (Konecny et al 1983) of PA has been extensively investigated, the molecular basis of substrate binding and catalysis, as well as the tridimentional structure of the protein remain to be determined. Nevertheless, it has been established that the catalytic mechanism progresses through an acyl-enzyme intermediate (Konecny et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it has been established that the catalytic mechanism progresses through an acyl-enzyme intermediate (Konecny et al 1983). Using site-directed reagents the existence of an essential serine residue which could be directly involved in the binding of the acyl moiety of the substrate (Siewinski et al 1984) has also been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the enzymic reaction mechanism of polymyxin acylase is different from those of usual aminoacylases. Similar enzymes, penicillin acylases, produced from E. COli,4) Bacillus megaterium, 5) or Xanthomonas citri 6 ) are also distinguishable from polymyxin acylase, because they are serine enzymes, inhibited by DFP or PMSF.…”
mentioning
confidence: 98%